The link between agricultural output and the states of poverty in the Philippines evidence from self-rated poverty data. - Mapa, Dennis S.; Lucagbo, Michael Daniel C.; Garcia, Heavenly Joy P. (2012)
The high poverty incidence in the country is a concern that needs to be addressed by our policy makers. Ofﬁcial poverty statistics from the National Statistical Coordination Board (NSCB) show that the reduction in poverty over the past two decades has been quite dismal from 38 percent in 1988 to 26 percent in 2009, or less than 1 percent reduction per year. Since poverty incidence has dynamic patterns, studies using ofﬁcial poverty data encounter difficulty because of alimited number of data points. This study builds econometric models in analysing the movement of poverty in the country using the quarterly self-rated poverty series of the Social Weather Stations. The ﬁrst model uses Markov Switching to determine the states of poverty. It assumes two states: high andmoderate states of poverty. A high 61 percent of the population considered themselves poor when the country is in the state of high poverty. In times of moderate poverty, 49.5 percent of the population consider themselves poor. The result shows thatonce the country is in the state of high poverty, it stays there for an average of 24 quarters, or six years, before moving out. The paper then builds a logistic regression model to show what determines the states of high poverty. The model shows that a 1 percent increase in agricultural output in the previous quarter reduces the probability of being in the high state of poverty by about 8 percentage points, all things being the same. The study shows that poverty incidence in the country is dynamic, and frequent monitoring through self-rated poverty surveys is important in order to assess the effectiveness of the government programs in reducing poverty. The self-rated poverty surveys can complement the ofﬁcial statistics on poverty incidence.
Keywords: Poverty; Poor; Agricultural productivity; Agricultural economics